Dental Care for Kabuki Syndrome Patient: a Case Rport (London Journal of Medical and Health Research, 2023)
Oral manifestations accompanying the syndromes may help dentists in diagnosing this syndrome. This article reports the case of a Syrian 4-year-old girl with Kabuki syndrome and the oral/dental aspects of this syndrome; including hypodontia with interdental spacing, abnormal tooth morphology.
Keywords: kabuki syndrome; early childhood caries; hypodontia